A Retrospective Review of Patient Records and Factors Associated with Decisions Made by Community Nurse-Paramedics' in Finland - Tuija Rasku; Mika Helminen; Marja Kaunonen; Elizabeth Thyer; Eija Paavilainen; Katja Joronen (MDPI AG, 2021)
Community paramedicine (CP) has extended the role of paramedics and the main goal is to provide non-emergency care, which reduces the visits to emergency departments. The aim of this study was to describe the Finnish CP and examine the factors that were involved in CNPs' decision-making processes. The study was based on data from 450 consecutive CP patient records from three hospital districts. A more detailed analysis was carried out on 339 cases in patients' homes and elderly care homes, and the data analysis included multivariate logistic regression to examine the impact of variables on the CNPs' decisions. These patients' most common health issues were general weakness (15.9%) and fever (10.6%), and over half (58.7%) could remain at home after the CP visit. There were five independent factors associated with the CNPs' decisions of the patient's care continuum: the hospital district, if the patient could walk, whether the troponin test was performed, a physician was consulted, and the nature of the task. CP units played a valuable role in non-emergency care. Understanding the factors associated with CNP decision-making can increase the safety and effectiveness of reducing hospital visits, by providing patient care at home, or in elderly care facilities.